ANALISIS HUBUNGAN KEPEMIMPINAN MELAYANI DENGAN KOMITMEN ORGANISASIONAL: STUDI PADA BPJS KESEHATAN KANTOR WILAYAH JAMBI - Suyadi Suyadi (Universitas Indo Global Mandiri)
This research examined the relationship between servant leadership (value people, develops people, builds community, displays authenticity, profides leadership, shares leadership) and organisational commitment in BPJS Kesehatan Kantor Wilayah Jambi. A total of 38 questionnaires were distributed to the employee BPJS Kesehatan Kantor Wilayah Jambi, 33 questionnaires were usable yielded a response rate of 86 %. The collected data were analysed using validity analysis, reliability analysis, descriptive analysis, correlation analysis using the SPSS 17.The research shows that from statistiki descriptive, based on the average value, mode, with standard Determination daviasi, seventh research variables associated with the item statement shows the positive direction and can be categorized good. The results showed that value people positively and significantly related to organizational commitment, which is obtained by the correlation coefficient was 0.487. The results showed that develops people positively and significantly related to organizational commitment, which is obtained by the correlation coefficient was 0.582. The results showed that builds community positively and significantly related to organizational commitment, which is obtained by the correlation coefficient was 0.606.While display authenticity positively and significantly related to organizational commitment, which is obtained by the correlation coefficient is 0,671.Whereas to provides leadership and significantly positively associated with organizational commitment which is obtained by the correlation coefficient was 0.639 and Shares leadership positively and significantly related to the value of the coefficient correlation is 0.542. Recommendations regarding the relationship of servant ledership with an organizational commitment. The importance of the attitude of the managers (leaders), provide positive behavior in employees that augur well for the progress of the organization in hope to be able to increase productivity. Keywords: Servant Leadership, Organizational Commitment